2013
DOI: 10.1111/desc.12096
|View full text |Cite
|
Sign up to set email alerts
|

Associations between children's socioeconomic status and prefrontal cortical thickness

Abstract: Childhood socioeconomic status (SES) predicts executive function performance and measures of prefrontal cortical function, but little is known about its anatomical correlates. Structural MRI and demographic data from a sample of 283 healthy children from the NIH MRI Study of Normal Brain Development were used to investigate the relationship between SES and prefrontal cortical thickness. Specifically, we assessed the association between two principal measures of childhood SES, family income and parental educati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
225
2
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(254 citation statements)
references
References 76 publications
24
225
2
3
Order By: Relevance
“…For comparison across participants, we created a study‐specific FA‐template based on all available images using Advanced Normalization Tools (ANTs) algorithms (Avants et al., 2014; Lawson, Duda, Avants, Wu, & Farah, 2013), which showed the highest accuracy in software comparisons (Klein et al., 2009; Murphy et al., 2011; Tustison et al., 2014). Individual images were transformed to template space using non‐linear registration with symmetric diffeomorphic normalization as implemented in ANTs (Avants, Epstein, Grossman, & Gee, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…For comparison across participants, we created a study‐specific FA‐template based on all available images using Advanced Normalization Tools (ANTs) algorithms (Avants et al., 2014; Lawson, Duda, Avants, Wu, & Farah, 2013), which showed the highest accuracy in software comparisons (Klein et al., 2009; Murphy et al., 2011; Tustison et al., 2014). Individual images were transformed to template space using non‐linear registration with symmetric diffeomorphic normalization as implemented in ANTs (Avants, Epstein, Grossman, & Gee, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…For instance, Tomarken and his colleagues found a relative left-frontal hypoactivity in lower SES adolescents (Tomarken et al, 2004). Furthermore, a recent study found that family SES significantly predicted cortical thickness in the right anterior cingulate gyrus and left superior frontal gyrus (Lawson et al, 2013). A growing body of evidence suggests that the mPFC plays an important role in emotional processing as well as the up-regulation and down-regulation of emotion (Kim & Hamann, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, educational studies indicate that there is a significant association between right hippocampal, amygdala volumes and paternal education levels (Hanson et al, 2011;Robert & House, 2000). A recent study examined a sample of 283 healthy children to investigate the relationship between SES and prefrontal cortical thickness, and they found that parental education significantly predicted cortical thickness in the right anterior cingulate gyrus and left superior frontal gyrus (Lawson, Duda, Avants, Wu, & Farah, 2013). In summary, SES is associated with the development of brain structures that play an important role in emotion, such as the hippocampus, anterior cingulate cortex, and amygdala.…”
Section: Introductionmentioning
confidence: 99%
“…In a study exploring effects of SES on cortical thickness in 283 healthy children and adolescents between ages 4 and 18 y of age, Lawson et al (83) found that lower parental education predicted decreased cortical thickness in anterior cingulate and superior frontal gyrus (prefrontal cortex), suggesting a link between SES and cognitive function. In this investigation, SES was defined by income-to-needs and parental education, however, only parental education was associated with outcomes.…”
Section: Neuroimaging In Older Children From Diverse Ses Environmentsmentioning
confidence: 99%